The Economic Consequences of the COVID-19 First Wave and the New International Scenarios: An Historical Dimension - Lepore, Amedeo; Palermo, Stefano; Pomella, Andrea (European Scientific Journal, ESJ, 2023)
The COVID-19 crisis is urging scholars to ponder the perspectives of the globalization process which started at the end of the XX Century, while the pandemic is increasing a sense of insecurity and uncertainty which has few precedents in the current age, pervading wider and wider sectors of the population. This paper focuses on analyzing the effects of the first wave of the pandemic (March 2020) using a historical-economic methodology based on a diachronic and comparative model. The effects of the crisis produced by the spread of Coronavirus are thus part of a wider analysis, in which the comparison of the behaviours of the different geoeconomic areas is carried out within the evolution of the long-term business cycles, considering both development and crisis phases. Finally, the article also proposes some hypotheses on the possible models of organization that the current globalization may encounter in the coming years.